EFISIENSI USAHA TANI PADI (Oryza sativa. L) DALAM PENGENDALIAN HAMA TERPADU (PHT) DI DESA KARANGKLESEM, KECAMATAN PAKUNCEN, KABUPATEN BANYUMAS - Mudmainah, Siti; Hapsari Arimurti , Niken (AGRO TATANEN | Jurnal Ilmiah Pertanian, 2025)
The Rice (Oryza sativa . L) is the main crop in Indonesia, almost half of Indonesia populasion consumes rice as a staple food. Especially rice, efforts need to be made to increase rice production, currently, it is hampered by pest attacks which can reduce agricultural production. The purpose of this study was to determine the characteristics of farmers, (2) know the factors that influence rice production, and (3) analyze the level of efficiency of techniques for using production factors in business farming. The research was conducted on rice crops in Karangklesem village, Pakuncen sub-district. Banyumas Regency, Respondent samples taken in this research were the purposive method, sampling was taken using a random sampling technique of 80 respondents. This research was conducted from July 2021 to October 2022. The results of this study show that average farmers carry out business farming on a land area of more than 1 hectare with farming experience of more than 15 years. The level of rice farming in Karangklesem village is technically efficient with an average technical efficiency level of 0.94 or 94 %. Production factors that have a real influence on rice farming production with integrated pest management (IPM) are chemical fertilizers, botanical pesticides, and chemical pesticides. The lowest level of efficiency of rice farming techniques was 0.81 and the highest level of efficiency was 0.99. average farmers have a technical efficiency level of 0.94 which means that rice production with the implementation of integrated pest management (IPM) reaches 94% of the potential rice production and there is still 6 % to increase production. Increase production with an average technical efficiency of 0.94. this shows that rice farming groups in Karangklesem village are profitable and farmers can still increase their incomes, and increase technical efficiency.